Bupivacaine Injection for Management of Lagophthalmos Due to Long-Standing Idiopathic Facial Nerve Palsy. Issue 6 (November 2015) - Rajabi, Mohammad Taher; Shadravan, Mahla; Mazloumi, Mehdi; Tabatabaie, Syed Ziaeddin; Hosseini, Seyedeh Simindokht; Rajabi, Mohammad Bagher
Abstract : Purpose: To report the results of bupivacaine injection into the orbicularis oculi muscle to treat lagophthalmos in patients with long-standing Bell palsy. Methods: In this prospective interventional case series, bupivacaine, 5 ml of a 0.750% solution, was injected into the preseptal and pretarsal area of the orbicularis oculi in each of 10 patients with idiopathic peripheral facial nerve palsy. The measures of vertical eyelid apertures during open and closed eyes were made before the procedure and 1, 3, and 6 months after injection. Results: A total of 10 eyes including 2 men and 8 women with an average age of 43 years (26–64 years) were studied. The mean amount of lagophthalmos before injection and after 6 months of follow up were 3.9 mm and 2.3 mm, respectively ( p = 0.01)). The mean amount of corneal exposure before injection and after 6 months of follow up was 1.05 mm and 0.25 mm, respectively ( p < 0.01). The mean scleral show in open eyes before injection and after 6 months of follow up were 1.20 mm and 0.75 mm, respectively ( p = 0.08). The mean scleral show in closed eyes before injection and after 6 months of follow up were 1.95 mm and 1.15 mm, respectively ( p = 0.01). All the patients reported significant decrease in epiphora. Conclusion: Bupivacaine injection in the paretic orbicularis oculi muscle improves eyelid closure and lagophthalmos and epiphora. Abstract : Bupivacaine injection in orbicularis muscle is a safe, effective, and simple method for management of lagopthalmos in patients with facial nerve palsy especially in patients with mild lagophthalmos.